Characteristics of Char and Tar from the Pyrolysis Process of Brem Waste with Temperature Variations Using a Rotary Kiln System - Majedi, Farid; Harito, Anatasya Bella Dwi; Ningrum, Fathonah Githa Setya; Ibadurrochim, Muhammad; Fauzi, Muhammad Arijal Fathurrohman; Inel, Limade Gie; Rosy, Karine Efrida; Daniswari, Dery Anton (Journal of Mechanical Engineering, Science, and Innovation, 2025)
One of the processes to obtain new renewable fuels is pyrolysis. This process produces alternative fuels, namely Char (charcoal), tar (bio-oil) and gas. Tar (bio-oil) can be processed into biodiesel. Pyrolysis is the process of breaking down (decomposing) biomass through a heating process with little or no oxygen. Research Pyrolysis of Rotary Kiln System with Brem, Plastic and Durian Peel Waste Biomass on Char and Tar Characteristics. This research was carried out by directly testing the pyrolysis of a rotary kiln system with brem, plastic and durian peel waste biomass. The test parameters use temperature variations of 523K, 573K, 673K, 773K, and 873K. Testing for each biomass is carried out separately, not mixed. The aim of the research is to determine the characteristics of char and tar from each biomass including calorific value, mass, volume and density. Research results the highest char calorific value is 11181.1 cal / gram with plastic waste biomass. The highest calorific value was obtained from tar from plastic waste, which was 14211.3 cal/gram. The highest density value was between 0.9-0.93 grams/ml in biomass from brem waste, plastic waste, durian skin waste.